Normal ranges of heart rate and respiratory rate in children from birth to 18 years of age: a systematic review of observational studies - Fleming, S; Thompson, M; Stevens, R; Heneghan, C; Plüddemann, A; Maconochie, I; Tarassenko, L; Mant, D (Elsevier, 2011)
Background: Although heart rate and respiratory rate in children are measured routinely in acute settings, current reference ranges are not based on evidence. We aimed to derive new centile charts for these vital signs and to compare these centiles with existing international ranges. Methods: We searched Medline, Embase, CINAHL, and reference lists for studies that reported heart rate or respiratory rate of healthy children between birth and 18 years of age. We used non-parametric kernel regression to create centile charts for heart rate and respiratory rate in relation to age. We compared existing reference ranges with those derived from our centile charts. Findings: We identified 69 studies with heart rate data for 143 346 children and respiratory rate data for 3881 children. Our centile charts show decline in respiratory rate from birth to early adolescence, with the steepest fall apparent in infants under 2 years of age; decreasing from a median of 44 breaths per min at birth to 26 breaths per min at 2 years. Heart rate shows a small peak at age 1 month. Median heart rate increases from 127 beats per min at birth to a maximum of 145 beats per min at about 1 month, before decreasing to 113 beats per min by 2 years of age. Comparison of our centile charts with existing published reference ranges for heart rate and respiratory rate show striking disagreement, with limits from published ranges frequently exceeding the 99th and 1st centiles, or crossing the median.